Optimal potential of cascading the hydro-power energy generation site, with a hydrokinetic turbine generation system. A case study analysis in the Southern African region - P.B. Ngancha; B.P. Numbi; K. Kusakana (Heliyon)
The production of hydroelectricity is well-established in many nations worldwide and has a reputation for being resilient, emitting little carbon dioxide, and having a long lifespan. This article begins by examining the hydropower sites capacity in the Southern African region and the potential for generation-site enhancement. The idea is developed from the emergence of new technologies in generating electricity, and the importance of generating more energy in meeting the growing demand. Hence, it is crucial to examine ways to recover the energy that is released shortly after the hydro-turbine rotates when generating energy, hydro flow in the form of kinetic energy of flowing water is released. This article proposes the installation of a hydrokinetic turbine in proximity down flow to the hydro-turbine to recuperate and maximize the surplus energy, using the same water flow. To achieve this goal, a model has been developed with MATLAB-Simulink software, in response to the research gap. This model will calculate the maximum flow rate and, consequently, the optimal location for a turbine in this cascaded configuration. The simulation's results show how adaptable the model is in suggesting a location for the turbine to be placed for maximum power generation. Simulations run in the cascaded hydropower and hydrokinetic setup system, with different scenarios of water volume release from the Dam. As a result, this study provides a sustainable framework for enhancing electricity generation through effective energy recovery while leveraging existing hydropower infrastructure.